THE TRANSACTIONAL ANALYSIS APPROACH IMPROVES STUDENTS' SOCIAL INTERACTION GROUP FORMAT - Putri Rahmayanti; Netrawati; Yeni Karneli (Literasi Nusantara, 2021)
Social interaction is the need of every human being. Humans as social beings cannot survive if they do not depend on each other. However, every time the relationship between datu with others causes miscommunication in the social interaction itself, giving rise to other problems. Thus social interaction can be done with transactional analysis counseling services group format. Through transactional analysis, it is possible to make improvements to the egos raised by individuals so that they no longer cause problems when interacting in their lives. The purpose of this research is to find out the contribution that group counseling services can make in increasing students' social interactions. The research methodology used is a literature study. Based on this research.